Are you experienced? Predator type and predator experience trade-offs in relation to tadpole mortality rates - Nomura, F.; do Prado, V. H. M. [UNESP]; da Silva, F. R. [UNESP]; Borges, R. E.; Dias, N. Y. N.; Rossa-Feres, D. de C. [UNESP] (Wiley-Blackwell, 2011)
Cryptic behavior and unpalatability are common defensive strategies that occur in different taxonomic groups, but the effectiveness of these defensive strategies is context dependent, varying with predator type and co-occurring species. We tested this assumption by measuring the mortality rates of Eupemphix nattereri (cryptic behavior) and Rhinella schneideri (unpalatable) tadpoles in association with the predatory fish Oreochromis niloticus (vertebrate) and the dragonfly larvae of Aeshna sp. (invertebrate). We designed a second experiment to evaluate whether fish predators are capable of learning to avoid unpalatable prey once they have encountered it. Our results showed that fish preyed selectively on palatable tadpoles, avoiding unpalatable tadpoles and that the odonate larvae were more efficient in preying on the more active unpalatable tadpoles and less efficient in capturing those tadpoles that presented cryptic behaviors. Additionally, our data suggest that the antipredator traits of tadpoles can interact with each other, with cryptic tadpoles showing lesser mortality when co-occurring with unpalatable tadpoles and odonate predators. Unpalatable tadpoles also increase the mortality of cryptic tadpoles in the presence of experienced fish predators. These prey traits interact in modifying the prey preference of the predator, which constitutes a prey-induced trait-mediated interaction (TMI). This type of TMI is dependent on the system complexity (number of predator and prey species interactions) and could define food web properties, such as the role of predators and the number of competitor species in the system.
Keywords: behavioral defenses; chemical defenses; cryptic behavior; tropical system; trait-mediated interactions; predator-prey interaction